Pengaruh Latihan Berpasangan Terhadap Keterampilan Passing Bawah Pada Siswa Ekstrakurikuler Bola Voli di SMK Negeri 1 Palopo - Sepang, Rosa Marten; Hidayat, Rachmat; Pribadi, Imam (Jurnal Porkes, 2025)
The purpose of this study was to examine the effect of paired training on lower passing skills in volleyball extracurricular students. This type of research is quantitative, using the pretest-posttest design experiment method. The subjects were all 12 volleyball extracurricular students at SMK Negeri 1 Palopo. The research instrument used a lower passing skill test. The data analysis technique used descriptive analysis, data normality test, homogeneity test, and paired sample t-test according to the significant level α = 0.05. The results showed that there was a significant effect in paired training on volleyball lower passing skills with a t value of 7.137 > t table 2.179 and sig. (2-tailed) is 0.000 < 0.05. The average value of the lower passing pretest is 2.108 and the average value of the lower passing posttest is 2.542 there is a difference between groups of -434. The conclusion is that there is a significant effect on paired training on volleyball extracurricular students at SMK Negeri 1 Palopo.